2021
DOI: 10.1155/2021/7158051
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Automatic Film Label Acquisition Method Based on Improved Neural Networks Optimized by Mutation Ant Colony Algorithm

Abstract: Nowadays, with the constant change of public aesthetic standards, a large number of new types and themes of film programs have emerged. For this reason, this paper proposes an improved neural network optimized by mutation ant colony algorithm for automatic acquisition of film labels, which not only overcomes the disadvantages of traditional neural network, such as difficulty in determining weights, slow convergence speed, and easiness to fall into local minimum, but also makes up for the shortcomings faced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The ant colony algorithm was proposed by Italian scholars Dorigo et al in the 1990s [36][37]. The ant colony algorithm is characterized by positive feedback, self-organization, parallelism, and robustness, and is often used to solve combinatorial optimization problems such as the traveler problem and the vehicle path problem.…”
Section: Ant Colony Algorithmmentioning
confidence: 99%
“…The ant colony algorithm was proposed by Italian scholars Dorigo et al in the 1990s [36][37]. The ant colony algorithm is characterized by positive feedback, self-organization, parallelism, and robustness, and is often used to solve combinatorial optimization problems such as the traveler problem and the vehicle path problem.…”
Section: Ant Colony Algorithmmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%